If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(2 + 5a) + -10 = 22 + 6a (2 * -3 + 5a * -3) + -10 = 22 + 6a (-6 + -15a) + -10 = 22 + 6a Reorder the terms: -6 + -10 + -15a = 22 + 6a Combine like terms: -6 + -10 = -16 -16 + -15a = 22 + 6a Solving -16 + -15a = 22 + 6a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6a' to each side of the equation. -16 + -15a + -6a = 22 + 6a + -6a Combine like terms: -15a + -6a = -21a -16 + -21a = 22 + 6a + -6a Combine like terms: 6a + -6a = 0 -16 + -21a = 22 + 0 -16 + -21a = 22 Add '16' to each side of the equation. -16 + 16 + -21a = 22 + 16 Combine like terms: -16 + 16 = 0 0 + -21a = 22 + 16 -21a = 22 + 16 Combine like terms: 22 + 16 = 38 -21a = 38 Divide each side by '-21'. a = -1.80952381 Simplifying a = -1.80952381
| 11/10(7/3) | | 8(4y-8)=12 | | (5x^2+7)-(-4y^2+7)= | | lr-3l=15 | | (1/2+3/5) | | 24-6j=36 | | 0.6(x+12)=1.6-(x+2) | | -1d/6=-4 | | 2y+1=3y+5 | | 1.6e-0.5=7.5 | | (1/2+3/5)/3/7 | | -7(5x-9)=27-4x | | 2/3x+7=28 | | 6x-(5x+4)=5x-24 | | x^2-10x+23= | | z-29=-35 | | -5n+14=-4n-16 | | -1(6x-2y)=-1(50) | | 4X+1/3=11 | | -2-2/3-3/5 | | x=0-4(7)(-3) | | 3/5(d/8+1/4)=9/16 | | 2x-13x(4-1)=-46 | | 3/8-1/2(3/4)^2 | | p=a+b-3 | | 10x+20=14x | | 2x-3x(4-x)=-46 | | 1/2(5/6)^2+2/9 | | 4y-3(y-4)+4=7 | | -2(-x+y)=-2(-5) | | .5x+.5x=1x+1 | | 40-(3c+4)=5c+20 |